Copy Number Variation of Human Satellite III (1q12) With Aging - Ershova, Elizaveta S.; Malinovskaya, Elena M.; Konkova, Marina S.; Veiko, Roman V.; Umriukhin, Pavel E.; Martynov, Andrey V.; Kutsev, Sergey I.; Veiko, Natalia N.; Kostyuk, Svetlana V. (Frontiers in Genetics, 2019)
Introduction. Human satellite DNA organized in long arrays in peri/centromeric heterochromatin. There is a little information about satellite CNVs with aging and replicative cell senescence (RS). Materials and Methods. Biotinylated pUC1.77 probe was used for the satellite III (f-SatIII) quantitation in leukocyte DNA by the non-radioactive quantitative hybridization for 557 subjects between 2 and 91 years old. The effect of RS and genotoxic stress (GS, 4µM or 6 µM K2CrO4) on the f-SatIII CNV was studied on the cultured skin fibroblast (HSF) lines of five subjects. Results. f-SatIII in leukocyte and HSFs varies between 5.7 to 40 pg/ng DNA. During RS the f-SatIII content in HSFs increased. During GS HSFs may increase or decrease f-SatIII content. Cells with low f-SatIII content have the greatest proliferative potential. F-SatIII CNVs in different individuals belonging to the different generations depends on year of their birth. Children (born in 2005 – 2015 years) differed significantly from the other age groups by low content and low coefficient of variation of f-SatIII. In the individuals born in 1912-1925 and living in unfavorable social conditions (FWW, the Revolution and the Russian Civil War, SWW) there is a significant disproportion in the content of f-SatIII. The coefficient of variation reaches the maximum values compared to individuals born in the period from 1926 to 1975. In the group of people born in 1990 - 2000 (Chernobyl disaster, the collapse of the Soviet Union and a sharp decline in the population living standard) again, there is a significant disproportion of individuals in the content of f-SatIII. A similar disproportion was observed earlier in the analysis of a group of individuals born in 1926 – 1975 who in their youth worked for a long time in high radioactive environment. Conclusion. In generations that were born and lived in childhood in a period of severe social perturbations or in conditions of environmental pollution we found a significant increase in leukocytes DNA f-SatIII variability. It is hypothesized that the change of the f-SatIII content in the blood cells reflects the body response to stress of different nature and intensity.